(3GdeQTO aj WH GdYjfs - (3YHO Gddg Hf YeQ Hf YHO GdcQje Hf eMeO Hf CMeO Hf CHj HcQ GdYjGTjs; (3CHh bShe , eMeO Hf bShe Hf GSde GdZGabj GdCfOdSj,J (B560 (3g` s ((3eGdbI s)
(3ChdgG (B:s
(3GHJGA GdRQY dG GHJZGA GdYTH, Ke GfgG dG JRGd JYTH dG eMGdI hcPdc GfJ jG Hfj eY GbJfGA GdGLQ dG JYOe GdefaYI s
(3BNQgG (B:s
(3hjWHNhjQaY dhbJ GdMGLI Gdjg Gf TGA Gddg JYGdiGfJgi hGdMeO ddg s
(3GKQ ajgG GdMQjb GdPi OjQ GdGSchQjGd aGJda GWQGagGs
(3GfXQ GjVG agQS GdWH HQbe (B225s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs